PENGARUH PEMBERIAN TEPUNG KEONG MAS DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHAN IKAN SIDAT (Anguilla bicolor) - Afra Nur Faridah; Yulfiperius Yulfiperius; Andriyeni Andriyeni (University of Prof. Dr. Hazairin, SH, 2018)
The purpose of this study was to determine the appropriate dosage of snail flour in fish feed for eel fish growth.This research was conducted in April - June 2017 which is located in Margasakti Village, Padang Jaya, North Bengkulu. The design used was Completely Randomized Design with 4 treatments and 6 replications.The treatment tested in this study was 58 gr/kg, 59/kg, 60/kg, and 61/kg grain snack dose.Containers used in the form of tarpaulins contained 24 containers. The test fish used amounted to 6 fish/containers. Parameters observed include growth of length and weight, feed conversion, feed efficiency, and survival.The results showed that giving of snail flour with different dose significantly influence to growth of length and weight, feed conversion, and feed efficiency.While on survival has no real effect. The proper dosage of snail flour for long and heavy growth, feed conversion, feed efficiency is60 gr/kg feed.